Determinantes do voto para deputado federal: relação entre emendas orçamentárias e desempenho eleitoral - Sanfelice, Viviane (2010)
Getting votes is crucial for any politician who is undergoing an election. Thus, this study is dedicated to investigate variables that affect the vote of incumbent deputy in Brazilian Congress who attempt to re-election, emphasizing the relationship between provision for budget amendments and electoral performance. To verify the importance of amendments on the electoral competition, the elections in the municipalities are also explored. The data used cover the elections and the Federal Budget for the period 1994 to 2006. Individual characteristics of members have strong explanatory power on the total votes obtained. Additionally, there is evidence of a local effect of the amendments over the voters and the relationship between deputy and municipality seems to determine most part of the municipal voting obtained in an attempt to re-election.